INHIBITORY EFFECTS OF POD EXTRACT OF ACACIA NILOTICA AGAINST SOME PATHOGENIC BACTERIA - Odewade, Joseph; Fasogbon, Albert; Afolabi, Olawale (FUDMA Journal of Sciences, 2020)
This study assessed the inhibitory effects of the pod extract of Acacia nilotica against some pathogenic bacteria (Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Pseudomonas aeruginosa, Staphylococcus aureus, Streptococccus pyogenes). Fresh pods of Acacia nilotica were air-dried and then ground into fine powder. Thereafter, pod powder was extracted using ethanol and distilled water in the ratio 3 to 2 (v/v). The crude extract was concentrated in vacuo and lyophilized. Afterwards, screened for phytochemicals and tested for antibacterial activity against the bacterial isolates. Antibacterial potential, minimum inhibitory concentrations (MIC), and minimum bactericidal concentrations (MBC) of the extract were determined using standard microbiological method. Zone of inhibition shown by the crude extract at 50 mg/mL on the isolates ranged between 10 mm and 18 mm while MIC ranged between 1.56 mg/mL and 25 mg/mL. Minimum bactericidal concentrations ranged between 3.13 mg/mL and 50.00 mg/mL. The phytochemical screening of the extract revealed the presence of tannins, alkaloids, flavonoids, saponins and cardiac glycosides. This study, therefore, showed that pod extract of Acacia nilotica exhibited appreciable inhibitory effects on the test isolates. Hence, there is need for in vivo studies to complement the present findings.